Characterization of seven psychoactive pharmaceuticals as N‐nitrosodimethylamine precursors during free chlorine and chlorine dioxide chlorination processes. Issue 1 (7th August 2018) - Lv, Juan; Li, Na
Abstract: BACKGROUND: Psychoactive pharmaceuticals used to treat neurological disorders are of great concern because of their frequent detection in the aquatic environment and drinking water. The possibility for concurrent formation of N‐nitrosodimethylamine (NDMA) from psychoactive pharmaceuticals during disinfection is still not well‐studied. In the present study, seven widely used psychoactive drugs were selected due to their possession of a DMA functional group. The NDMA formation potentials of the selected drugs were assessed during free chlorine (NaOCl) and chlorine dioxide (ClO2 ) disinfection processes. The influence of several parameters (i.e. disinfectant dose, pH and water matrix) was investigated to better understand the reaction between the drugs and disinfectants that cause the formation of NDMA. RESULTS: The NDMA molar yields of seven pharmaceuticals were higher than 2%. NDMA formation was independent of the pH value, and more NDMA formation was observed during free chlorine chlorination. NDMA generation was enhanced when the selected pharmaceuticals were present in real water matrices, especially in secondary effluent. CONCLUSION: This study demonstrated that the seven selected psychoactive pharmaceuticals containing dimethylamine groups can serve as NDMA precursors during free chlorine and chlorine dioxide chlorination processes. ClO2 was a proper disinfectant for controlling NDMA formation during chlorination. © 2018 Society of Chemical Industry